Working capital management at Advanced Network systems Vietnam Limitted Company - Nguyễn, Thị Kim Dung (2020)
The research objective of the thesis is to propose solutions to enhance working capital management at ANSV Co., Ltd. in the coming time. To achieve this goal, the dissertation performs the following research tasks:-Systematizing theoretical issues about working capital management-Analyzing and evaluating the current status of working capital management at Advanced Networks System Viet Nam Co., Ltd.-Proposing solutions to improve working capital management at Advanced Networks System Viet Nam Co., Ltd.